Indonesian Perceptions Toward Materials in Context of Culture - Intan Prameswari; Haruo Hibino; Shinichi Koyama (Journal of Visual Art and Design, 2017)
Human attitudes, behavior and perceptions are shaped by their culture. Culture is deeply embedded in all aspects of human life, including design development. This study was conducted to discover perceptions regarding five chair materials (wood, rattan, bamboo, metal, and plastic) in a cultural context in an Indonesian student sample group. A previous study suggested that Indonesian participants have a positive attitude toward natural chair materials such as wood and rattan. The experimental results of the present follow-up study suggest that rattan is the chair material most representative of Indonesian culture. As a heterogeneous country, Indonesia has multiple ethnicities, which influences the perception of which material best represents Indonesian culture.